ANALYSIS OF THE INFLUENCE OF LABOR MARKET AND WORK ENVIRONMENT AS CONSIDERATIONS FOR ACCOUNTING STUDENTS CAREER INTEREST IN PUBLIC ACCOUNTANT - Shendy, Velisa Enjjelita; Seputro, Davina Febrianti (PT Naureen Digital Education, 2024)
This study aims to analyze the effect of the job market and work environment as a consideration of accounting students' career interest in the public sector. This study uses a quantitative approach with the independent variables in this study being the job market and work environment, while students' career interest in the public sector is the dependent variable. Existing data were collected through questionnaires distributed to undergraduate accounting students in Surabaya. From the questionnaires distributed, the respondent data that can be researched is obtained as much as 101 respondent data. The results of the analysis show that the job market that offers career stability, security, and clear career development opportunities has a significant influence on students' interest in choosing a career in the public sector. In addition, a supportive work environment, including work-life balance and a good working climate, also play an important role in influencing students' decisions. These findings provide important insights for universities and government agencies to design strategies that can increase the attractiveness of the public sector as a career choice for accounting graduates.